2018
DOI: 10.1186/s12991-018-0220-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fish oil omega-3 fatty acids on reduction of depressive symptoms among HIV-seropositive pregnant women: a randomized, double-blind controlled trial

Abstract: BackgroundGlobally, it is known that HIV-infected pregnant women are prone to depressive symptoms. Research evidences also suggest that nutrient deficiencies may enhance the depressive illness, and that fish oil omega-3 fatty acids may alleviate the depressive symptoms. The aim of this study was to assess the effect of fish oil omega-3 eicosapentaenoic acid-rich supplements on depressive symptoms among HIV-seropositive pregnant women.Trial designA randomized double-blinded controlled trial with two parallel gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 58 publications
0
6
2
Order By: Relevance
“…The study’s total sample size ranged from 32 to 1140, intervention sample sizes ranged from 19 to 578 and control group sample sizes ranged from 13 to 562. The majority of studies (n = 22, 73.33 %) reported on interventions for depression [33‐55]. Major depressive disorder was confirmed using diagnostic interviews such as SCID or MINI in three studies [34‐36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study’s total sample size ranged from 32 to 1140, intervention sample sizes ranged from 19 to 578 and control group sample sizes ranged from 13 to 562. The majority of studies (n = 22, 73.33 %) reported on interventions for depression [33‐55]. Major depressive disorder was confirmed using diagnostic interviews such as SCID or MINI in three studies [34‐36].…”
Section: Resultsmentioning
confidence: 99%
“…This review revealed six studies which evaluated complementary and alternative interventions for depression. The interventions evaluated included omega‐3 fatty acids [49,52], physical exercise [33] an herbal supplement [38] and yoga [37]. The study evaluating physical exercise and one study evaluating omega‐3 fatty acids did not register any advantage over placebo.…”
Section: Resultsmentioning
confidence: 99%
“…The BDI-II scale has 21 questions, scores ranging from 0 to 63, and is used to screen for depression [19]. The BDI-II scale has been validated for prenatal depression [20] and used for prenatal depression in countries such as Ethiopia and Kenya [21,22]. For EPDS, thresholds of 10 and 13 are commonly used to screen for depression with 10 having a higher sensitivity and 13 having a higher specificity [23].…”
Section: Depression Measurementsmentioning
confidence: 99%
“…Effect of fish oil omega-3 fatty acids on reduction of depressive symptoms among HIVseropositive pregnant women: a randomized, double-blind controlled trial [42].…”
Section: Pilot Randomized Controlledmentioning
confidence: 99%